Nodulation, physiological attributes, water use efficiency and nutrient uptake of chickpea (Cicer arietinum) genotypes under different environment - Reeta; Parveen Kumar (Annals of Agricultural Research, 2022)
The field experiment was conducted in concrete drought plots at CCS Haryana Agricultural University, Hisar during rabi season of 2017-18 to study nodulation, physiological parameters, nutrient uptake and economics of chickpea (Cicer arietinum L) genotypes under different environment in factorial randomized block design (FRBD) with three replications. In one block two irrigations, one at pre-flowering and other at pod development stage were applied and in other block no post sowing irrigation was applied. The number and weight of nodules, nutrient uptake, total water use, water use efficiency and benefit – cost ratio were found significantly higher under wet environment as compared to dry environment. Among genotypes, phosphorus uptake in seed, and straw were significantly higher in H 13-36 and H 12-63 as compared to other genotypes. Potassium uptake was not significantly affected by genotypes. Total water use was higher under genotype H12-26 and H13-09 but water use efficiency was recorded higher under genotype H 13-36 as compared to other genotypes.